Resorbable magnesium metal membrane for sinus lift procedures: a case series - Akiva Elad; Luka Pul; Patrick Rider; Svenja Rogge; Frank Witte; Dražen Tadić; Eitan Mijiritsky; Željka Perić Kačarević; Larissa Steigmann (BMC, 2023)
Abstract Background The purpose of this case series was to demonstrate the use of a magnesium membrane for repairing the perforated membrane in both direct and indirect approaches, as well as its application in instances where there has been a tear of the Schneiderian membrane. Case presentation The case series included four individual cases, each demonstrating the application of a magnesium membrane followed by bone augmentation using a mixture of xenograft and allograft material in the sinus cavity. In the first three cases, rupture of Schneiderian membrane occurred as a result of tooth extraction, positioning of the dental implant, or as a complication during the procedure. In the fourth case, Schneiderian membrane was perforated as a result of the need to aspirate a polyp in the maxillary sinus. In case one, 10 mm of newly formed bone is visible four months after graft placement. Other cases showed between 15 and 20 mm of newly formed alveolar bone. No residual magnesium membrane was seen on clinical inspection. The vertical and horizontal augmentations proved stable and the dental implants were placed in the previously grafted sites. Conclusion Within the limitations of this case series, postoperative clinical examination, and panoramic and CBCT images demonstrated that resorbable magnesium membrane is a viable material for sinus lift and Schneiderian membrane repair. The case series showed successful healing and formation of new alveolar bone with separation of the oral cavity and maxillary sinus in four patients.